Children's exposure to domestic violence: theory, practice, and implications for policy - Carmel, Yifat (Routledge, 2024)
"This book bridges together research, theory, and practice to offer future directions for new treatment policy and context-based intervention with children exposed to domestic violence. Centering the voices of children, this book aims to reveal and fill in the gaps of knowledge concerning deep levels of the exposure to the domestic violence phenomenon. The book begins with a critical review of the whole field, covering theory, research, intervention, and policy. The author then puts forward a new data-based conceptualization for understanding this field of abuse and its application in practice. Drawing on her rich academic and clinical experience, Carmel includes treatment recommendations, planning, and intervention strategies as well as suggestions for how to deal with the phenomenon at the policy level in the legal, social, community, and education fields. Calling for the involvement of legal, educational, and community systems, this book is essential reading for researchers in psychology, law, social work, education, gender studies, sociology, as well as therapeutic practitioners, such as clinicians, educational consultants, art therapists, and policy makers"--